Markers of Inflammation and Fibrosis in Alcoholic Hepatitis and Viral Hepatitis C - Neuman, Manuela G. (Hindawi Publishing Corporation, 2012)
High levels of profibrinogenic cytokine transforming factor beta (TGF-β), metalloprotease (MMP2), and tissue inhibitor of matrix metalloprotease 1 (TIMP1) contribute to fibrogenesis in hepatitis C virus (HCV) infection and in alcohol-induced liver disease (ALD). The aim of our study was to correlate noninvasive serum markers in ALD and HCV patients with various degrees of inflammation and fibrosis in their biopsies. Methods. Serum cytokines levels in HCV-infected individuals in the presence or absence of ALD were measured. Student's-t-test with Bonferroni correction determined the significance between the groups. Results. Both tumor-necrosis-factor- (TNF)-α and TGF-β levels increased significantly with the severity of inflammation and fibrosis. TGF-β levels increased significantly in ALD patients versus the HCV patients. Proinflammatory cytokines' responses to viral and/or toxic injury differed with the severity of liver inflammation. A combination of these markers was useful in predicting and diagnosing the stages of inflammation and fibrosis in HCV and ALD. Conclusion. Therapeutic monitoring of TGF-β and metalloproteases provides important insights into fibrosis.